2019
DOI: 10.3390/ma12071006
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Ti-6Al-4V Alloy by Electrical Discharge Coating Process Using Partially Sintered Ti-Nb Electrode

Abstract: In the present research, a composite layer of TiO2-TiC-NbO-NbC was coated on the Ti-64 alloy using two different methods (i.e., the electric discharge coating (EDC) and electric discharge machining processes) while the Nb powder were mixed in dielectric fluid. The effect produced on the machined surfaces by both processes was reported. The influence of Nb-concentration along with the EDC key parameters (Ip and Ton) on the coated surface integrity such as surface topography, micro-cracks, coating layer thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…The experimental researches are at initial stages regarding the surface modification through EDM in context of biocompatibility. EDM has been used for coating [26,34,35], particle migration [36,37], layer quality improvement [30,38,39], and nano-surface treatment [30,[40][41][42] for biomedical implants surface treatment of titanium alloys [43].…”
mentioning
confidence: 99%
“…The experimental researches are at initial stages regarding the surface modification through EDM in context of biocompatibility. EDM has been used for coating [26,34,35], particle migration [36,37], layer quality improvement [30,38,39], and nano-surface treatment [30,[40][41][42] for biomedical implants surface treatment of titanium alloys [43].…”
mentioning
confidence: 99%
“…They reported that both grinding and etching-grinding techniques removed the recast layer, and hence improved the surface integrity. Prakash et al [16] proposed altering the EDM process for coating TiO 2 -TiC-NbO-NbC on Ti-64. They reported that this process improved the mechanical properties on the machined surface.…”
mentioning
confidence: 99%
“…Authors have proved that the application of an abrasive machining tool equipped with the ultraviolet-curable resin bonding during lapping process enabled an approximately 10% lower surface roughness parameter Ra and 25% less weight loss of the workpiece than those obtained in the iron plate lapping process. Prakash et al [4], in their study, employed two methods (electric discharge coating (EDC) and electric discharge machining processes (EDM)) to coat a composite layer TiO 2 -TiC-NbO-NbC on the Ti-64 alloy. The conducted research revealed that the application of the EDC process with a high peak current and high Nb-powder concentration enabled the formation of a crack-free thick layer (215 µm) on the workpiece surface.…”
Section: Ofmentioning
confidence: 99%